The Impact of Globalization on the Economy and Entrepreneurship in the Creative Industry Sector: A Case Study in Jakarta City - Judijanto, Loso; Musprihadi, Ribut; Semmawi, Ramli; Harahap, Rahma Hayati (West Science Journal Economic and Entrepreneurship, 2023)
Using a quantitative methodology based on structural equation modelling with partial least squares (SEM-PLS), this study examines the relationship between globalization, entrepreneurship, and local economic indicators within Jakarta's creative economy. The intricate dynamics of the creative economy were revealed through the observations of a sample of 150 participants drawn from a variety of sub-sectors. Strong validity and reliability were demonstrated by the measuring approach, which also successfully captured the latent dimensions of entrepreneurship, globalization, and local economic indicators. Significant direct effects of globalization and entrepreneurship on regional economic indicators were found by the structural model analysis. Furthermore, it was shown that entrepreneurship acted as a partial mediator, enhancing the effects of globalization on the regional economy. The results provide policymakers, industry stakeholders, and creative entrepreneurs with important takeaways. They also serve as a basis for well-informed plans aimed at promoting sustainable economic development within Jakarta's thriving creative sector.